Implementing the ASEAN Agreement on Disaster Management and Emergency Response for Better Coordination and Simplification Procedures - Triyana, Heribertus Jaka; Harjono, Novita Putri; Mcdermott, Ronan (Jambe Law Journal, 2022)
This article aims to critically examine implementation of the ASEAN Agreement on Disaster Management and Emergency Response (AADMER) to cope with humanitarian assistance caused by disasters, complex emergencies and conflicts in South East Asian countries. It focusses on how the ASEAN member States initiate and implement coordination and simplification of procedures on how to deliver humanitarian assistance to victims once those situations are declared as regional concern. The analysis in this paper is mainly construed by normative legal research relied on information of facts and information of legal bases in order to find out legal gaps, ambiguity, overlapping institutions and conflict of norms on coordination and procedures between national and regional regulations, policies, programs and actions. It provides framework for analysis on how constructive engagements under the AADMER generate a distinctive legal feature for regional concerns dealing with humanitarian issues in South East Asian Countries. This article reveals that effective coordination and simplification of procedures are back bones for the AADMER implementation. Factually, regulatory impacts assessments have been assessed and factually carried out by ASEAN member States in terms of increasing their understanding, allocation of all available resources and reducing potential risks when they create and implement their national rules and regulation on disaster, complex emergency and conflicts. However, at the same time, they tend to be reluctant to take measures on underlying necessity of legitimate reasons, authority as well as their advanced resources. It is necessary to be shared to reduce capacity gaps for better effective coordination and simplification of procedures due to their narrowed understanding of state’s sovereignty to shield their unwillingness to cooperate